Pemanfaatan Limbah Kulit Kopi sebagai Upaya Pemberdayaan Ibu-ibu Rumah Tangga di Desa Latimojong, Kabupaten Enrekang - Andi Nur Fajri Suloi (Institut Pertanian Bogor, 2019)
The Village of Latimojong, Sub-district of Buntu Batu is one of the largest coffee producing areas in Enrekang Regency. Coffee bean processing gives a by-product in the form of coffee husk which has the potential to become waste. Alternative solutions that can be done is to process the coffee skin waste into a product in the form of coffee skin powder that can be used by the community, especially housewives as coloring agents or scents in food products. This program aims to empower housewives through the utilization of coffee skin waste. The method used is counseling and demonstration with several stages, namely pre-activity, socialization, implementation, and evaluation of activities. The results of the implementation of this activity is to increase community knowledge and skills about processing coffee skin waste, producing a product derived from coffee skin waste, and provide economic value to the skin of the coffee.